METABOLIC TREATMENT WITH L-CARNITINE IN ACUTE ANTERIOR ST SEGMENT ELEVATION MYOCARDIAL INFARCTION: A RANDOMISED CONTROLLED TRIAL - G. Tarantini; D. Scrutinio; P. Bruzzi; L. Boni; P. Rizzon; S. Iliceto (Российский кардиологический журнал, 2011)
Administration of L-carnitine in patients with anterior acute myocardial infarction (AMI) prevents left ventricular remodelling. Current study was aimed to assess the effect of L-carnitine administration on mortality and heart failure in patients with anterior AMI. CEDIM 2 trial was a randomized, double-blind, multicentre, placebo-controlled trial planned to enrol 4,000 patients with acute anterior AMI. The trial was interrupted after the enrolment of 2,330 patients because of the lower than expected enrolment rate. The primary end point was a composite of death and heart failure at 6 months; 5-day mortality was the secondary end point. During the 6-month follow-up, the primary endpoint was not significantly different between the L-carnitine and placebo group (9,2 vs. 10,5%, p=0,27). A reduction in mortality was seen in the L-carnitine arm on day 5 (secondary end-point) from randomization (HR=0,61, 95% CI 0,37–0,98, p=0,041). In CEDIM 2 trial L-carnitine therapy led to a reduction in early mortality (secondary end-point) without affecting the risk of death and heart failure at 6 months in patients with anterior AMI, leading to a non-significant finding with respect to the primary end-point.